Methionine Supplementation Options in Poultry - Kalbande, V.H.; Ravikanth, K.; Maini, S.; Rekhe, D.S. (International Journal of Poultry Science, 2009)
Methionine is essential or limiting amino acid for poultry. An experiment was conducted to determine the comparative efficacy of DL-methionine and herbal methionine supplement on growth and performance of broiler chickens. Three hundred commercial broiler (VenCobb) chicks were procured and randomly divided into three groups (n = 100), one control (T0) and two treatments (T1 and T2). All the groups were offered standard maize-soyabean meal based ration. T1 was offered herbal sources of methionine (Methiorep®, supplied by Ayurvet Ltd., India) @1kg/tonne of feed and T2 was administered DL- methionine@ 1 kg/tonne of feed from 0-42 days. A significant improvement in overall growth and performance was observed in birds supplemented with methionine. This study demonstrates that herbal methionine can replace DL-methionine very efficiently when used at the rate 1 g/kg diet of commercial broiler chicken.